2022
DOI: 10.3389/fgene.2022.929477
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs in maternal plasma as potential biomarkers of early pregnancy in sheep

Abstract: MicroRNA (miRNA) plays an important role in the control of gene expression and is implied in many biological functions, including embryo implantation and development. The aim was to assess plasma miRNA profiles during the peri-implantation and ascertain potential candidate miRNA markers for early pregnancy diagnosis in ovine plasma. The plasma samples were obtained from a total of 24 ewes on days 12 (pre-implantation; P12, n = 4), 16 (implantation; P16, n = 4) and 22 (post-implantation; P22, n = 4) after matin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…In recent years, numerous studies that uncovered many miRNAs have identified circulating plasma miRNAs ( Hitit et al, 2022a ). Villous trophoblast-derived miRNAs are transported through maternal blood in extracellular vesicles or connected to them ( Kotlabova et al, 2011 ; De los Santos Funes et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous studies that uncovered many miRNAs have identified circulating plasma miRNAs ( Hitit et al, 2022a ). Villous trophoblast-derived miRNAs are transported through maternal blood in extracellular vesicles or connected to them ( Kotlabova et al, 2011 ; De los Santos Funes et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…To thaw the plasma, we used a dry bath set to 20 degrees. Subsequently, 250 ul of plasma was processed through the miRCURY RNA Isolation Kit—Biofluids (Exiqon #300112 Vedbaek- Denmark) in compliant with the manufacturer's instructions to isolate total cell-free RNA ( Hitit et al, 2022a ). DNA contamination was removed from samples using on-column DNase according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the traits, phenotypes associated with reproductive outcome and fertility are of major interest to cattle producers, mainly because of the high production loss from a heifer of low reproductive potential. Specifically in reproductive biology, miRNAs have been demonstrated to be important regulators of embryonic development in humans and livestock, such as predicting pregnancy outcomes ( Ioannidis and Donadeu, 2016 ; Hitit et al, 2022 ), embryo viability ( Pohler et al, 2017 ) and implantation ( Kose et al, 2022 ), and endometrial receptivity ( Zang et al, 2021 ). Moreover, miRNAs regulate the gene targets by repressing or stimulating their expression ( Orang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We deemed genes as putative targets of a particular miRNA only if predicted so by all three tools (Oliveira et al, 2017). To refine our results, we filtered out putative target genes that had an energy score >-15 kcal/mol (all three tools), and a sequence complementary score <150 (miRanda) (Hitit et al, 2022).…”
Section: Mirna Target Gene Predictionmentioning
confidence: 99%